Manajemen Humas Pemerintah Kota Bekasi dalam Mewujudkan Program Digital PR - Fitri, Farhan Kurnia; Muhtadi, Asep Saeful (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This study aims to determine the process of public relations management at the stage of fact finding, planning and programming, taking action and communication and evaluating the program carried out by the Public Relations of the Bekasi City Government in realizing a digital PR program. This research uses descriptive-qualitative method with primary and secondary data sources. Data collection techniques were carried out through observation, interviews and documentation studies. The results of the study show a strategic management process with stages; First, the fact finding stage which consists of situation analysis and informal research; Second, the planning and programming which consists of six stages of planning and programming; Third, the taking action and communication is the stage of implementing digital PR through the management of E-Kliping and E-Release on the website sakerhumas.bekasikota.go.id; Fourth, the stage of evaluating the program is carried out in three strategic stages.